2023
DOI: 10.1155/2023/9467314
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Distribution, and Factors Associated with Vector-Borne Pathogen Infections in Pet Dogs from Different Geoclimatic Zones in Sri Lanka

Ushani Atapattu,
Vito Colella,
Andrew Worsley
et al.

Abstract: Vector-borne pathogens (VBPs) cause significant diseases in dogs in the tropics. In Sri Lanka, the scarce availability of previous studies on canine VBPs has hampered an accurate evaluation of their prevalence in pet dog populations. In this study, we collected demographic, clinical, and environmental data together with whole blood from 423 pet dogs from three geoclimatic zones in Sri Lanka. All blood samples were screened using a previously validated multiplex qPCR assay to detect the six most prevalent canin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…This study also identified many common canine VBPs that are typically found in temperate to tropical environments, including the bacterial pathogens A. platys, E. canis and M. haemocanis, as well as the apicomplexans B. gibsoni, B. vogeli and H. canis [ 4 , 31 , [82] , [83] , [84] ]. Many of these VBPs are transmitted by Rhipicephalus linnaei ticks, with pathogen species such as E. canis causing severe and potentially fatal infections in canines, whilst VBPs such as B. vogeli and A. platys typically only impact the health of puppies, or adults in the context of coinfections [ [85] , [86] , [87] , [88] ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study also identified many common canine VBPs that are typically found in temperate to tropical environments, including the bacterial pathogens A. platys, E. canis and M. haemocanis, as well as the apicomplexans B. gibsoni, B. vogeli and H. canis [ 4 , 31 , [82] , [83] , [84] ]. Many of these VBPs are transmitted by Rhipicephalus linnaei ticks, with pathogen species such as E. canis causing severe and potentially fatal infections in canines, whilst VBPs such as B. vogeli and A. platys typically only impact the health of puppies, or adults in the context of coinfections [ [85] , [86] , [87] , [88] ].…”
Section: Discussionmentioning
confidence: 99%
“…Many of these VBPs are transmitted by Rhipicephalus linnaei ticks, with pathogen species such as E. canis causing severe and potentially fatal infections in canines, whilst VBPs such as B. vogeli and A. platys typically only impact the health of puppies, or adults in the context of coinfections [ [85] , [86] , [87] , [88] ]. In addition, some of these pathogens may be transmitted non-vectorially, for example the potentially fatal piroplasmid B. gibsoni can be transmitted through fighting and aggressive interactions, whilst the transmission of canine haemotropic mycoplasmas is a debated field of research with strong evidence to suggest that these pathogens can be transmitted in the absence of arthropod vectors [ 83 , [89] , [90] , [91] ]. The identification of these canine VBPs in Bhutan is not surprising given that A. platys , Babesia spp., E. canis , and H. canis have been identified previously in northeastern India within regions directly bordering the south of Bhutan where our study was conducted [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations